MATERIAL AND NON-MATERIAL CULTURE OF THE POPULATION OF THE CHIROQCHI BAKLIGY DURING THE PERIOD OF THE BUKHARA EMIRATE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article studies the cultural life of the Chiroqchi Beklig region, located in the southwestern part of Kashkadarya. It highlights the historical, literary, artistic and educational aspects of the Chiroqchi Beklig, and talks about its rich cultural heritage, which was formed under the influence of various civilizations. The article also emphasizes the important role of the Jadid movement in the modernization of education. Information is also provided about the traditions, holidays and family values in the Chiroqchi Beklig, and the importance of education and national identity is indicated. The article generally describes how the cultural life of this region has developed over the centuries and continues to this day.